Analisis Unsur Abu Cangkang Kelapa Sawit Hasil Pirolisis Menggunakan X-Ray Fluorescence (XRF) - Natalia Pangaribuan; Mahyunis Mahyunis (CV. IRA PUBLISHING, 2026)
The palm oil industry generates substantial amounts of solid waste in the form of palm kernel shells, which are not optimally utilized. This study aims to analyze the effects of pyrolysis temperature and time on the elemental composition of Tenera variety oil palm shell ash using X-ray fluorescence (XRF) analysis. The study used a two-factor randomized block design with temperature (400°C, 450°C, 500°C) and time (4, 5, 6 hours) as factors. The results showed that increasing temperature and time decreased the solids yield from 76% to 54% and increased the ash content. The highest silica content was obtained at 500°C, 43.35%. This study confirms the potential of oil palm shell ash as an alternative silica source for construction material applications.